2009
DOI: 10.1155/2009/479512
|View full text |Cite
|
Sign up to set email alerts
|

On PHY and MAC Performance in Body Sensor Networks

Abstract: The last few decades have seen considerable research progress in microelectronics and integrated circuits, system-on-chip design, wireless communication, and sensor technology. This progress has enabled the seamless integration of autonomous wireless sensor nodes around a human body to create a Body Sensor Network (BSN). The development of a proactive and ambulatory BSN induces a number of enormous issues and challenges. This paper presents the technical hurdles during the design and implementation of a low-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In this scenario, E[P(d)] ≈ P env (for both the intended transmitter and interferers) and the link probability of success can be expressed as follows: It can be observed that the terms in the second and third lines at the right-hand side of (20) are similar to (15) and (16). Therefore, by using the same derivation of Section 3-A, with…”
Section: L(d) [Db]mentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, E[P(d)] ≈ P env (for both the intended transmitter and interferers) and the link probability of success can be expressed as follows: It can be observed that the terms in the second and third lines at the right-hand side of (20) are similar to (15) and (16). Therefore, by using the same derivation of Section 3-A, with…”
Section: L(d) [Db]mentioning
confidence: 99%
“…The slotted ALOHA multiple access scheme [19] was recently proposed by the IEEE 802.15.6 working group as one of the reference medium access control (MAC) schemes for the wireless body networks in the context of the narrowband communications [20]. In particular, in each time slot, the nodes are assumed to transmit independently with a certain fixed probability [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar concept exists in the domain of wireless communication where the wireless radio is turned on and off depending on whether there is any communication to be performed or not, respectively. For example, radio sleep scheduling has been considered for BSNs [8,9].…”
Section: Energy Perspectivementioning
confidence: 99%
“…Towards this objective, one option is to reduce the power demand of the computing operations so that it is always within the available power (or reduces the grid power demand as far as possible). In this regard, strategies for sustainable computing have focused on processor level power management schemes such as frequency control, voltage control, or sleep state scheduling [7], Medium Access Control (MAC) sleep scheduling of the wireless radio [8,9] communication among the sensors, and amortization of the wireless communication energy in sensor networks with less expensive computation [10]. However, design of sustainable CPSs requires a holistic approach which is aware of the limited available energy from the scavenging sources.…”
Section: Introductionmentioning
confidence: 99%
“…These traffic patterns are periodic, so TDMA-based MAC protocols [27,28,29] are usually used in BSNs to reduce packet collisions. However, these protocols cannot avoid the interference between nearby BSNs.…”
Section: Solutions For Reliable Bsn Communicationmentioning
confidence: 99%